2011
DOI: 10.1371/journal.pntd.0001046
|View full text |Cite
|
Sign up to set email alerts
|

Use of Saliva for Early Dengue Diagnosis

Abstract: BackgroundThe necessity of a venous blood collection in all dengue diagnostic assays and the high cost of tests that are available for testing during the viraemic period hinder early detection of dengue cases and thus could delay cluster management. This study reports the utility of saliva in an assay that detects dengue virus (DENV)–specific immunoglobulin A (Ig A) early in the phase of a dengue infection.Methods and FindingsUsing an antigen capture anti-DENV IgA (ACA) ELISA technique, we tested saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…In the pilot study and the group of infants Ͻ15 months of age, we observed significant correlations between IgG levels in sera and oral fluid (r ϭ 0.456, P Ͻ 0.0001, and r ϭ 0.598, P Ͻ 0.0001, respectively). A similar correlation was also reported for other infectious diseases, such as malaria (11), tetanus antitoxin (19), rubella (20), and dengue (for IgA) (9). In our target population of 70 uninfected infants Ͻ15 months of age, a parallel decline in IgG was observed in the two biological fluids, and the line of the moving average illustrated the similarity in the patterns of IgG evolution in oral fluid and sera (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…In the pilot study and the group of infants Ͻ15 months of age, we observed significant correlations between IgG levels in sera and oral fluid (r ϭ 0.456, P Ͻ 0.0001, and r ϭ 0.598, P Ͻ 0.0001, respectively). A similar correlation was also reported for other infectious diseases, such as malaria (11), tetanus antitoxin (19), rubella (20), and dengue (for IgA) (9). In our target population of 70 uninfected infants Ͻ15 months of age, a parallel decline in IgG was observed in the two biological fluids, and the line of the moving average illustrated the similarity in the patterns of IgG evolution in oral fluid and sera (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…This result is similar to those seen in previous studies. [5][6][7]9,22 In contrast, Mohiti-Ardekani et al demonstrated that s-IgA levels in diabetic patients were higher than in non-diabetics. 1 Other studies have also found higher s-IgA levels in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Other studies have also reported conflicting results with regards to s-IgA levels and their relationship to various diseases. 6,7 The current study aimed to compare s-IgA levels between healthy subjects and T2DM patients and determine the association between s-IgA levels and various oral and dental manifestations in diabetic patients. This relationship could help determine the prognosis of oral diseases in diabetic patients and serve as a guide for their dental care.…”
Section: Advances In Patient Care -Determination Of the Salivary Compmentioning
confidence: 99%
“…For malaria, IgG antibodies directed against specific Plasmodium falciparum antigens can be detected in saliva and were found to correlate strongly with levels in plasma (80). Similarly, using antigen capture methods, IgA antibodies specific to dengue virus that correlate well with early secondary infection have been found in saliva (81). In contrast, M. tuberculosis and many viruses, including Ebola virus, HSV, EBV, HHV, and CMV, are most reliably detected directly using PCR methodologies (82,83,84,85,86,87).…”
Section: Infectious Diseasementioning
confidence: 99%